Understanding children and adolescents - Schickedanz, David I.; Schickedanz, Judith A.; Forsyth, Peggy D.; Forsyth, G. Alfred. (Allyn and Bacon, 2001)
Research, theory, and biology. Infants and toddlers. Preschool children. School-age children. Adolescents.